Effect of topical latanoprost on choroidal thickness and vessel area in Guinea pigs. (December 2022) - El-Nimri, Nevin W.; Jiang, Liqin; Dahanayake, Dinasha; Sweidan, Sami; Smith, Benjamin E.; Wildsoet, Christine F.
Abstract: The aim of this study was to investigate the effect of latanoprost, an ocular hypotensive agent and prostaglandin analog, on choroidal thickness and structure in young adult guinea pigs. Young (three-month-old) guinea pigs (n = 10) underwent daily monocular treatment with topical 0.005% latanoprost for 2 weeks, followed by a washout period of 2 weeks. Tonometry (iCare) and retinoscopy were undertaken to monitor intraocular pressure (IOP) and refractive error (recorded as spherical equivalent refractive error; SER), respectively. Axial length (AL) and choroidal thickness (ChT) were measured using high frequency A-scan ultrasonography, with additional ChT data, as well as choroidal vessel (ChV) areas obtained from posterior segment imaging using Spectral Domain-Optical Coherence Tomography (SD-OCT). Image J was used to analyze SD-OCT images. As expected, latanoprost significantly reduced IOP in treated eyes. Mean interocular IOP difference (±SE) changed from −0.40 ± 0.31 mmHg at baseline to −2.23 ± 0.43 mmHg after 2 weeks of treatment (p = 0.05). However, SER and AL were unaffected; interocular difference changed from 0.41 ± 0.58 to 0.38 ± 0.43 D and from −0.002 ± 0.02 mm to −0.007 ± 0.01 mm (p > 0.05), respectively. Latanoprost had minimal effect on ChT. Interocular ChT differences were 0.01 ± 0.06 μm at baseline and 0.04 ± 0.06 μm after 2 weeks of treatment (SD-OCT; p > 0.05). However, treated eyes had significant increased ChV areas; interocular differences changed from −0.76 ± 69.2 to 100.78 ± 66.9 μm 2 after treatment (p = 0.04). While this study was limited to otherwise untreated young adult guinea pigs, the possibility that choroidal vessel enlargement contributes to the previously reported inhibitory effect of topical latanoprost on myopia progression in young guinea pigs warrants investigation. Highlights: Topical latanoprost resulted in enlargement of choroidal vessels in guinea pigs. Latanoprost did not significantly affect the overall choroidal thickness. Refractive errors and axial length were unaffected after using latanoprost.